CONSTRUCTION SEMI-AUTOMATIC SLITTING MACHINE FOR ELECTRODES OF CYLINDER BATTERY - Hendi Lilih Wijayanto; Rahul Wijayanto (BRILIANT: Jurnal Riset dan Konseptual, 2026)
Semi-automatic cutting machines for battery electrodes are important tools in the development of the battery manufacturing industry, which aim to ensure precision and efficiency in the battery electrode cutting process. This research focuses on the design and construction of a machine capable of cutting cylindrical battery electrodes with high accuracy and good consistency. The machine consists of several main components such as an electric motor, pulleys, belts, shafts, cutting blades, hollow steel, steel plates, and bolts, which are systematically integrated to achieve optimal cutting results. The electric motor with a rotational speed of 1350 RPM serves as the main drive of the machine. This motor drives the pulley and belt to transmit power to the cutting blade, which is used to precisely cut the electrodes. A 20 mm diameter steel shaft was selected to connect the pulley and cutting blade, ensuring stable and efficient power transmission during operation. The research results show that this machine is capable of cutting a cylindrical battery electrode cutting with a width of 65 mm and a length of 950 mm in a single cut with a cutting time of 3 seconds. The machine's construction successfully cuts the electrode according to the specified specifications. Test results from four cuts indicate that the tool functions optimally and meets the standards.